SISTEM PAKAR MENDIAGNOSA PENYAKIT HEWAN TERNAK KAMBING DENGAN MENGGUNAKAN METODE CERTAINTY FACTOR - Sari, Nur Falita; Sulindawaty, Sulindawaty (Majalah Ilmiah Kaputama, 2019)
Expert systems are systems that try to adopt human knowledge into computers, so that computers can solve problems as is usually done by experts. Expert system is a computer program that simulates the judgment and behavior of humans or organizations that have expert knowledge and experience in a particular field. In an expert system has many algorithms, one of which is the intelligence factor. Certainty Factor states trust in an event in accordance with the evidence and judgment of an expert. This method uses a value in assuming an expert's degree of confidence in the data. The design of goat disease diagnosis application is made to be useful for users / breeders, which is to make it easier to get information by using the application as a consultation media.